1997
DOI: 10.1590/s0100-879x1997000400011
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial control of water and saline intake: role of <FONT FACE=Symbol>a</font>2-adrenoceptors

Abstract: Water and saline intake is controlled by several mechanisms activated during dehydration. Some mechanisms, such as the production of angiotensin II and unloading of cardiovascular receptors, activate both behaviors, while others, such as the increase in blood osmolality or sodium concentration, activate water, but inhibit saline intake. Aldosterone probably activates only saline intake. Clonidine, an α 2 -adrenergic agonist, inhibits water and saline intake induced by these mechanisms. One model to describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Bilateral injections of RX 821002 into the LPBN abolished the effects of noradrenaline and α-methylnoradrenaline in the same area on 0.3 M NaCl (2,39). The increase in sodium intake after LPBN moxonidine or noradrenaline injection in fluid-depleted rats (2,38,39) sharply contrasts with the inhibitory effect that α 2 -adrenoceptor activation in the forebrain has on sodium appetite and thirst (1,9,11-13). Therefore, forebrain and hindbrain (or more specifically LPBN) α 2 -adrenergic mechanisms play opposite roles in water and sodium intake (38,39).…”
Section: Role Of Lpbn α2-adrenoceptors On Sodium Appetitementioning
confidence: 92%
See 3 more Smart Citations
“…Bilateral injections of RX 821002 into the LPBN abolished the effects of noradrenaline and α-methylnoradrenaline in the same area on 0.3 M NaCl (2,39). The increase in sodium intake after LPBN moxonidine or noradrenaline injection in fluid-depleted rats (2,38,39) sharply contrasts with the inhibitory effect that α 2 -adrenoceptor activation in the forebrain has on sodium appetite and thirst (1,9,11-13). Therefore, forebrain and hindbrain (or more specifically LPBN) α 2 -adrenergic mechanisms play opposite roles in water and sodium intake (38,39).…”
Section: Role Of Lpbn α2-adrenoceptors On Sodium Appetitementioning
confidence: 92%
“…Its effects depend on the area of the encephalon studied, the type of treatment the animal receives, and the receptors involved (for a review see Refs. 1,2). Early studies using mixed α 2 -adrenergic and imidazoline receptor agonists, like clonidine and moxonidine, injected into the lateral and third cerebral ventricles, septal area, lateral preoptic area, and lateral hypothalamus showed that they are effective in inhibiting water and sodium intake induced by different stimuli (1,3-10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations